2011
DOI: 10.1103/revmodphys.83.1301
|View full text |Cite
|
Sign up to set email alerts
|

Colloquium: Hidden order, superconductivity, and magnetism: The unsolved case ofURu2Si2

Abstract: This Colloquium reviews the 25 year quest for understanding the continuous (2 nd ) order, meanfield-like phase transition occurring at 17.5 K in URu 2 Si 2 . Since ca. ten years the term hidden order (HO) has been coined and utilized to describe the unknown ordered state, whose origin cannot be disclosed by conventional solid-state probes, such as x-rays, neutrons, or muons. HO is able to support superconductivity at lower temperatures (Tc ≈ 1.5 K) and when magnetism is developed with increasing pressure both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
440
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(460 citation statements)
references
References 193 publications
(381 reference statements)
18
440
1
1
Order By: Relevance
“…Single-crystal X-ray diffraction measurements revealed the expected ThCr 2 Si 2 type structure with lattice constants a U = 4.133 (3) Å and c U = 9.58 (1) Å and a Th = 4.189 (2) Å and c Th = 9.745 (6) Å for URu 2 Si 2 and ThCr 2 Si 2 , respectively. These values are similar to those reported earlier [1][2][3][4]16,26]. For both materials, the direction perpendicular to the crystal surface is the c-axis, in agreement with earlier results from molten indium flux growth of URu 2 Si 2 ( Figure 1f) [16].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Single-crystal X-ray diffraction measurements revealed the expected ThCr 2 Si 2 type structure with lattice constants a U = 4.133 (3) Å and c U = 9.58 (1) Å and a Th = 4.189 (2) Å and c Th = 9.745 (6) Å for URu 2 Si 2 and ThCr 2 Si 2 , respectively. These values are similar to those reported earlier [1][2][3][4]16,26]. For both materials, the direction perpendicular to the crystal surface is the c-axis, in agreement with earlier results from molten indium flux growth of URu 2 Si 2 ( Figure 1f) [16].…”
Section: Resultssupporting
confidence: 82%
“…χ(T) shows pronounced anisotropy where the c-axis is the easy axis, which is characteristic of the paramagnetism in URu 2 Si 2 [3,4]. The inverse magnetic susceptibility χ −1 reveals a Curie-Weiss temperature dependence χ(T) = C/(T−θ), and a fit to the data yields µ eff = 3.72 µ B and θ = −90.5 K. Near T coh,Ø ≈ 55 K, χ(T) evolves through a broad hump that may be associated with the onset of Kondo coherence [1][2][3][4]. At the "hidden-order" temperature T 0 , χ(T) is abruptly reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the intensive investigation that followed its discovery nearly thirty years ago, the nature of the order parameter is still unknown. The phase is now known as a Hidden Ordered Phase [7]. Recently, Okazaki et al have measured the magnetic susceptibility [8] of ultra-small samples using highly sensitive magnetic torque measurements and have reported that, below the transition, the susceptibility becomes anisotropic in the a − b plane.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 25 years, virtually every imaginable experimental technique has been applied in attempts to reveal the nature of this state, but its origin remains an open question. [28,29] The coupling of 'something' to charge degrees of freedom clearly opens a gap in the electronic spectrum below 17.5 K, but the unanswered question is what is that 'something' The development of significantly improved resolution in angle-resolved photoemission spectroscopy and the application of new resonant x-ray and scanning tunneling techniques, among others, are ruling out some of the many theoretical suggestions for its origin and maybe are giving clues to what it might be. Perhaps, the answer lies in the simultaneous coupling among multiple degrees of freedom that compete or cooperate in such a way that the coupling to a single degree of freedom is not dominant.…”
Section: Couplingsmentioning
confidence: 99%